Analytical determination of parameters of the hydropneumatic source of seismic waves - S. P. Ekomasov (Известия высших учебных заведений: Геология и разведка)
The analytical expressions for the calculation of the key parameters for the design a working body of new hydropneumatic source of seismic waves are given. The solution of the problem of the quantitative assessment of the characteristics of the power impulses generated by the source at the contact place of a shock plate with soil is given. An experiment has confirmed good convergence of calculated and experimental values.